(untitled) (Islamic Sciences Journal, 2023)
This is a research on adolescence between Islamic studies and contemporary studies, through which I wanted to make a comparison between the two studies in order to find out the comprehensiveness of our true religion and take into account all stages of the human being and not neglect any of it. Research method: the inductive approach. The results that I stood upon, which include: 1_ Adolescence is a stage of life in which a person approaches puberty as he moves from childhood to adulthood. 2_ That adolescence usually extends from the age of twelve to the age of twenty-one approximately. 3- Adolescence is one of the most dangerous stages if the parents do not deal with the teenager properly. 4- Preparation and pre-awareness for the child before entering adolescence is very important.